The Notion of Power in the Theories of Bourdieu, Foucault and Baudrillard - Gečienė, Ingrida (Sociologija. Mintis ir veiksmas, 2002)
The concept of “power” seems to be one of the basic and most attractive but also one of the most difficult to define in contemporary sociology. In this essay it will be concentrated on quite distinct from traditional perspective notion of power, presented by the theories of Bourdieu’s, Foucault’s and Baudrillard’s, what will give possibility also to follow the emergence of post-modern discourse on power. There are a number of distinctive (or even contradictory) perspectives of power, mostly rooted in the Weber’s and/or Marx’s theories. Among these new theories it is possible to indicate one more radical critique, which puts accent on the more or less invisible (indirect and symbolic) character of power, and thus unites such different theories as Bourdieu’s, Foucault’s and Baudrillard’s. The main incitement for this approach was the need to look at power from perspective different than the juridical-political theory of sovereign power and an analysis of the state and to consider the material techniques of power that are not compatible with relations of sovereignty. Thus here the main question emerges: how does a social system in which a substantial section of the population is obviously disadvantaged and exploited survive without its rulers having to depend on physical coercion for the maintenance of order?